Effects of Supplementation With Antioxidant Agents on Sleep in Autism Spectrum Disorder: A Review - Zambrelli, Elena; Lividini, Althea; Spadavecchia, Sofia; Turner, Katherine; Canevini, Maria Paola (Frontiers in Psychiatry, 2021)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition, whose etiology remains poorly understood in most cases. Several genetic, epigenetic and environmental factors have been implicated in ASD pathogenesis and numerous studies have provided evidences for increased levels of oxidative stress and reduced antioxidant capacity in patients with ASD. Recent clinical trials explored supplementation with antioxidant agents as a potential therapeutic strategy for ASD, investigating the impact of this treatment on behavioral symptoms and on most common comorbidities of the disease, including sleep disturbances. Among all medical conditions associated to ASD, sleep problems are highly prevalent and are supposed to be positively related to the severity of the disease. Moreover, studies on animal models support the hypothesis of a relationship between oxidative stress and sleep deprivation. The aim of this review is to summarize the current state of the literature on the effect of antioxidant treatment on sleep disturbances in patients with ASD. Twenty-one articles were included in final synthesis. Of them, 15 studies involved Melatonin, 1 Tryptophan and 5 focused on supplementation with other antioxidant agents (namely Coenzyme Q10, L-Carnosine, Luteolin and Quercetin). Despite the high prevalence of comorbid sleep troubles in ASD, there is a paucity of data on the efficacy of antioxidant agents in those patients. Further research is needed to better define the role of antioxidants agents as adjunctive therapy in the management sleep disorders in children and adolescents affected with ASD.